Corrosion behavior of tantalum coatings on AISI 316L stainless steel substrate for bipolar plates of PEM fuel cells. (14th August 2020) - Manso, A.P.; Marzo, F.F.; Garicano, Xabier; Alegre, Cinthia; Lozano, Antonio; Barreras, Félix
Abstract: Corrosion resistance of tantalum coatings 30 μm thick deposited by chemical vapor deposition on SS316L coupons has been evaluated by electrochemical impedance spectroscopy (EIS). To this end, anodic and cathodic operating conditions of proton exchange membrane fuel cells (PEMFC) have been simulated in a three-electrode heated corrosion cell. Interfacial contact resistance (ICR), contact angle and durability tests have been performed in long-term tests (>100 h) polarizing the electrode to 1.193 V vs. Ag/AgCl. Results obtained by different experimental techniques show a dense coating structure with a high polarization resistance, mainly formed by surface crystals of α-Ta (bcc), Ta2 O5 and carbon. An atomic ratio (in %) of oxide to metallic species (Taox /Tamet ) of 4.8 was verified from XPS spectra, which is slightly increased to 6.23 after the anodizing treatment. The modified surface composition yielded a coating capacity higher than the amorphous oxide, favoring the in-plane electrical conduction. After the treatment, no noticeable changes were observed neither in surface morphology nor in contact angle (>90°). ICR values in the range of 22.3–32.6 mΩ cm 2 were obtained for a clamping pressure of 140 N cm −2 . No morphological changes or loss of coating adherence were observed during the long-term tests. Highlights: Corrosion resistance of tantalum coating on stainless steel was evaluated. Operating conditions of PEMFC were simulated in a three-electrode corrosion cell. SEM images show a compact surface Ta coating without cracking straight paths. No morphological changes or loss of coating adherence were observed in long-term tests. The coexistence of Ta oxide and metallic Ta improves the electrical properties of the coating.